2021
DOI: 10.3390/ijms22168946
|View full text |Cite
|
Sign up to set email alerts
|

Th17-Related Cytokines as Potential Discriminatory Markers between Neuromyelitis Optica (Devic’s Disease) and Multiple Sclerosis—A Review

Abstract: Multiple sclerosis (MS) and Devic’s disease (NMO; neuromyelitis optica) are autoimmune, inflammatory diseases of the central nervous system (CNS), the etiology of which remains unclear. It is a serious limitation in the treatment of these diseases. The resemblance of the clinical pictures of these two conditions generates a partial possibility of introducing similar treatment, but on the other hand, a high risk of misdiagnosis. Therefore, a better understanding and comparative characterization of the immunopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 151 publications
(186 reference statements)
0
20
0
Order By: Relevance
“…Interleukin-17A (IL-17A) is an effective proinflammatory cytokine produced by Th17 cells and IL-17-secreting CD8+T cells ( 85 ). It promotes the pathophysiology of autoimmune diseases and may mediate delayed inflammation by inducing neutrophils and monocytes to recruit chemokines at inflammatory sites ( 85 ).…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-17A (IL-17A) is an effective proinflammatory cytokine produced by Th17 cells and IL-17-secreting CD8+T cells ( 85 ). It promotes the pathophysiology of autoimmune diseases and may mediate delayed inflammation by inducing neutrophils and monocytes to recruit chemokines at inflammatory sites ( 85 ).…”
Section: Cytokinesmentioning
confidence: 99%
“…Interleukin-17A (IL-17A) is an effective proinflammatory cytokine produced by Th17 cells and IL-17-secreting CD8+T cells ( 85 ). It promotes the pathophysiology of autoimmune diseases and may mediate delayed inflammation by inducing neutrophils and monocytes to recruit chemokines at inflammatory sites ( 85 ). A recent study has shown that IL-17 impairs myelin regeneration and promotes myelin damage through oligodendrocyte/myelin injury mediated by increasing voltage-gated K+ channel 1 ( 86 ).…”
Section: Cytokinesmentioning
confidence: 99%
“…Naive T-helper cells differentiate into a new lineage called Th17 and have the capacity to produce large amounts of IL-17, a cytokine linked to autoimmune diseases [ 67 , 106 ]. IL-6 signaling involving Th17 cells and Th17-associated cytokines may play a crucial role in the pathogenesis of NMOSD ( Figure 1 ) [ 66 , 107 , 108 , 109 , 110 ]. Apart from IL-17, Th17-cell differentiation may be induced by IL-6, IL-23, and transforming growth factor β1 [ 111 , 112 ].…”
Section: Potential Biomarkers In Nmosdmentioning
confidence: 99%
“…Third, the coinjection of AQP4-IgG antibodies and complement can activate the complement system in rats but not in mice and may lead to underestimation of the complement inhibitory function. Finally, EAE models in rats are Th1-cell-mediated, whereas AQP4-specific T cells in NMO reportedly show a preferential involvement of Th17/Th2 lymphocytes including IL-6- and Th17-polarizing cytokine interactions [ 65 , 108 , 178 ].…”
Section: Limitations Of the Animal Models Of Nmomentioning
confidence: 99%
“…These demonstrations indicated that FOXP3-EXOs treatment could efficiently ameliorate the development of EAE by, at least partly, regulating the immune homeostasis of Th/Treg. It is well-established that Th1 and Th17 cells not only represented a major initiator but was also a participant in the pathogenesis and progression of MS as well as its animal model-EAE: 1) In MS, raised proportion of Th1 and Th17 cells in the peripheral blood and increased concentrations of Th1-and Th17-related cytokines such us IFN-γ, TNF-α, IL-6, IL-17, IL-21, IL-22, and IL-23 in the serum had been mentioned in numerous previous studies [2,9,29]. 2) MOG-specific-Th1 and Th17 cells could induce typical adoptive transfer EAE [30].…”
Section: Treatment With Foxp3-exos Inhibits the Development Of Eaementioning
confidence: 99%